2018
DOI: 10.1037/pas0000577
|View full text |Cite
|
Sign up to set email alerts
|

Suicide risk assessment: Trust an implicit probe or listen to the patient?

Abstract: Previous research suggests implicit cognition can predict suicidal behavior. This study examined the utility of the death/suicide implicit association test (d/s-IAT) in acute and prospective assessment of suicide risk and protective factors, relative to clinician and patient estimates of future suicide risk. Patients (N = 128; 79 female; 111 Caucasian) presenting to an emergency department were recruited if they reported current suicidal ideation or had been admitted because of an acute suicide attempt. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 57 publications
(93 reference statements)
0
20
0
Order By: Relevance
“…For instance, Chiurliza et al (2018) found that the S-IAT was not related to a history of suicidal ideation among 1,548 U.S. military service members. In the same way, Running head: IMPLICIT ASSOCIATION, SUICIDE, AND REPLICATION 6 Harrison, Stritzke, Fay, and Hudaib (2018) found little evidence that the S-IAT prospectively predicted suicide risks in a clinical sample, above and beyond clinician prediction.…”
Section: Suicide-implicit Association Testmentioning
confidence: 99%
“…For instance, Chiurliza et al (2018) found that the S-IAT was not related to a history of suicidal ideation among 1,548 U.S. military service members. In the same way, Running head: IMPLICIT ASSOCIATION, SUICIDE, AND REPLICATION 6 Harrison, Stritzke, Fay, and Hudaib (2018) found little evidence that the S-IAT prospectively predicted suicide risks in a clinical sample, above and beyond clinician prediction.…”
Section: Suicide-implicit Association Testmentioning
confidence: 99%
“…Third, individuals—and, in particular, adolescents—may not have the self-awareness to report accurately on the cognitive processes underlying their behavior (Nock et al ., 2010 ; Weil et al ., 2013 ). To address these limitations, researchers examining risk for suicidal behaviors have begun to use cognitive tasks involving implicit measurements that do not rely on self-report (Cha et al ., 2010 ; Barnes et al ., 2016 ; Harrison et al ., 2018 ). One such task is a version of the Implicit Association Test (IAT) that measures response latencies to speeded judgments of pairs of death-related and self-related words (Nock et al ., 2010 ; Glenn et al ., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Harrison, Stritzke, Fay, and Hudaib (2018) reported that clinician prediction did not significantly predict future attempts at three-and six-month follow-up (p ¼ 0.16 and p ¼ 0.30, respectively), despite significantly predicting suicidal ideations at both timepoints (p ¼ 0.049 and p ¼ 0.011, respectively). Another study found that, while clinician assessment of risk was moderately accurate at predicting future suicide attempts (AUC ¼ 0.728, 95%CI 0.66-0.79), it was not effective at predicting deaths from suicide (AUC ¼ 0.546, 95%CI 0.36-0.73) (Randall et al, 2019).…”
Section: Suicide and Self-harm Related Outcomesmentioning
confidence: 84%